Análisis y diseño de prototipo de sistema de control para compañías de transporte de carga pesada. - Valverde, Galo (2009)
The research project was based on a market analysis, an analysis of how systems behave decision-making and technical analysis and this can prove that the Information Systems in a high degree conducive to the Managers or Administrators to effective decision making and information systems help the efficient management of business logistics processes in Heavy Duty Transportation. In this analysis we obtained results for the sector alarming little or no automation of logistics processes and thus administrators and managers do not have the necessary information to make decisions. The project's main purpose of planning, setting strategy and technological development of a control system such as entrepreneurship, there was a solution for companies engaged in freight operations with a comprehensive tool for managing the processes involved in this activity. The prototype of the Control System of the Transport Company to automate processes optimally to be a tool that collected the main requirements of these companies.